LEGAL INTERPRETATION AND JUSTICE: ANALYZING COURT DECISIONS IN DRUG-RELATED DIVORCE CASES IN BANDA ACEH - Iqbal, Muhammad; Abbas, Syahrizal; Hanapi, Agustin (Universitas Syiah Kuala, 2025)
This article analyses the decision-making processes of Banda Aceh Syariah Court judges in divorce cases related to drug abuse. By examining the elements of judicial deliberation and the types of legal interpretation employed, the study highlights how different interpretative approaches influence court rulings. The normative research methodology, utilizing statutory, conceptual, and case approaches, ensures a thorough understanding of legal principles and their application in specific cases. Data collection through documentation and interviews with judges, clerks, and legal experts provides valuable insights into judicial reasoning and practical considerations. The findings indicate that discrepancies in court decisions primarily stem from varying interpretations of key evidentiary elements, such as witness testimony, the petition (petitum), pragmatic considerations, and laboratory evidence of narcotics. The use of authentic interpretation, especially grammatical interpretation, demonstrates the judges effort to adhere to the original text and intent of Islamic law. The employment of analogical interpretation reflects an adaptive approach to address complex issues like drug abuse, ensuring that decisions are both legally sound and contextually relevant.The study affirms that these interpretative methods align with Islamic legal principles, particularly the concepts of maslahat (public interest) and mafsadat (harm), which serve as guiding criteria in legal reasoning. By integrating juridical, philosophical, and sociological perspectives, the judges decisions exemplify a holistic approach to justice that balances legal consistency with societal needs. This nuanced understanding underscores the importance of interpretative flexibility within Islamic jurisprudence to effectively address contemporary issues.